Surabaya sebagai Sebuah Destinasi Wisata Wellness - Andrean Loenardus Bandoro (PolimdoSains, 2018)
Wellness Tourism is a tourism involves people who travel to pursue activities that maintain or enhance their personal health and wellbeing, and who are seeking unique, authentic or location-based experiences/therapies. Surabaya has a huge amount of wellness business sites scattered all over the city but there are very less foreign visitors. And in the local market, wellness business is perceived very negatively: very expensive and there is always hidden sex service. This research is done with the purpose to present some specific considerations and recommendations for the Government and the Wellness industry to pursue to position themselves to take the most advantage of wellness tourism opportunities. Methods used are: Library study, Direct Observation, Interview with business owners, therapist, local and foreign customers. Research result suggests that City Government shall play an active role to put scattered wellness businesses in an area together with hotels, health shops, and money changer and market this area through Tour Planner, Tourism Information Office, and Tourism Web. They have to be managed anyway to avoid hidden prostitutes. That serves 2 benefits: they are undercontrol and they will become an obvious wellness tourism destination.